Christina Stead and the Matter of America - Morrison, Fiona, 1969- (Sydney studies in Australian literature., 2019)
In this examination of Stead's American work, Fiona Morrison explores Stead's profound engagement with American politics and culture and their influence on her "restlessly experimental" style. Through the turbulent political and artistic debates of the 1930s, the Second World War, and the emergence of McCarthyism, the "matter" of America provoked Stead to continue to create new ways of writing about politics, gender and modernity.